Studi Literatur: tentang Berbagai Jenis Pupuk dan Respon Morfologi Tanaman Kelapa Sawit - Mula Narju; Ikhlas Hamzani; Rahmat Barona (Jurnal Pertanian Khairun, 2026)
Abstract Oil palm (Elaeis guineensis) is a vital commodity in Indonesia, playing a crucial role in the economy and global food security. To enhance productivity, early-stage oil palm cultivation integrated with proper fertilization is a necessity. Fertilizers provide essential nutrients required for optimal growth, with various types of fertilizers—both organic and inorganic—exerting different impacts on plant morphology. Research indicates that applying fertilizers with correct principles can enhance oil palm growth, agronomic characteristics, and productivity. This study aims to identify the types of fertilizers used in oil palm cultivation, analyze the morphological responses of plants to different fertilizer types, and compare the effectiveness of organic and inorganic fertilizers. Organic fertilizers, derived from natural materials, function to enhance soil fertility, improve microorganism activity, and support the health of roots, stems, and leaves. Meanwhile, inorganic fertilizers provide rapid and effective nutrients for the plants. The morphological response to fertilization is reflected in improved root, stem, and leaf growth, which contributes significantly to overall plant health and productivity. When used simultaneously, organic and inorganic fertilizers can create a synergy, delivering necessary nutrients while building soil conditions that support more optimal root growth. With a profound understanding of fertilization practices and their impacts, the findings of this study are expected to provide insights into more effective and sustainable oil palm cultivation practices. Keywords: Oil palm, fertilization, organic fertilizer, inorganic fertilizer, morphological response.